Rebaudiosides T and U, minor C-19 xylopyranosyl and arabinopyranosyl steviol glycoside derivatives from Stevia rebaudiana (Bertoni) Bertoni. (March 2017) - Perera, Wilmer H.; Ghiviriga, Ion; Rodenburg, Douglas L.; Alves, Kamilla; Bowling, John J.; Avula, Bharathi; Khan, Ikhlas A.; McChesney, James D.
Abstract: Two diterpene glycosides were isolated from a commercial Stevia rebaudiana leaf extract. One was found to be 13-[(2- O -β-d -glucopyranosyl - 3- O -β-d -glucopyranosyl-β-d -glucopyranosyl)oxy] ent -kaur-16-en-19-oic acid-(2- O -β-d -xylopyranosyl-3- O -β-d -glucopyranosyl- β-d -glucopyranosyl) ester (rebaudioside T), whereas the other was determined to be 13-[(2- O -β-d -glucopyranosyl - 3- O -β-d -glucopyranosyl-β-d -glucopyranosyl)oxy] ent -kaur-16-en-19-oic acid-(6- O -α-l -arabinopyranosyl-β-d -glucopyranosyl) ester (rebaudioside U). In addition, five C-19 sugar free derivatives were prepared and identified as follows: 13-[(2- O -α-l -rhamnopyranosyl-β-d -glucopyranosyl)]oxy]kaur-16-en-19-oic acid (dulcoside A1 ); 13-[(2- O -β-d -xylopyranosy-3- O -β-d -glucopyranosyl-β-d -glucopyranosyl)oxy]kaur-16-en-19-oic acid; 13-[(2- O -β-d -xylopyranosyl - β-d -glucopyranosyl-)oxy]kaur-16-en-19-oic acid; 13-[(2- O -β-d -glucopyranosyl - 3- O -β-d -glucopyranosyl-β-d -xylopyranosyl-)oxy]kaur-16-en-19-oic acid (rebaudioside R1 ) and 13-[(2- O -6-deoxy-β-d -glucopyranosyl-3- O -β-d -glucopyranosyl - β-d -glucopyranosyl)oxy]kaur-16-en-19-oic acid, respectively. Chemical structures were determined by NMR experiments. HPLC analyses were also useful to differentiate different steviol-C13 sugar substituent patterns by elution position. Graphical abstract: Two steviol glycosides (1, 2 ), together with five compounds with no sugar moiety at C-19, were isolated from commercial Stevia rebaudiana crude extracts or prepared from known natural glycosides. The presence of an arabinose moiety in steviol glycosides is also reported. Highlights: Two steviol glycosides were isolated from Stevia rebaudiana commercial crude extract. Four compounds were prepared from natural steviol glycosides. Chemical structures were elucidated by 1D and 2D NMR. An arabinopyranosyl steviol glycoside subfamily was described, with rebaudioside U as head of series.